Hyperurikemia in chronic kidney disease stage 4 — the issue of suitability of urate-lowering therapy - Melnyk, I.I. (KIDNEYS, 2023)
For almost 20 years, the issue of hyperuricemia has been studied in nephrology, rheumatology, cardiology, endocrinology, and neurology areas of medicine. In all countries of the world, new aspects of this clinical symptom are being revealed almost simultaneously, some facts are being disproved, and updated practical recommendations are being implemented. The main medical axiom now is that hyperuricemia is a symptom of chronic kidney disease (CKD) of any stage, but the pathogenetic mechanisms of the effect of a high uric acid level on kidney function are not known for sure. It is necessary to correct its level under certain clinical and laboratory criteria in order to reduce the risk of cardiovascular disease and the risk of increased mortality, to influence the course of diabetes and possibly prevent obesity. There are still a lot of questions and unexplained facts. For example, what is the role of hyperuricemia in CKD, what level of uric acid reduction is safe and appropriate? What is the causal relationship between uric acid levels and CKD progression? Is the treatment of asymptomatic hyperuricemia effective for absolutely all patients? Is a differentiated approach to lowering the level of uric acid necessary depending on the stage of CKD? When should one take into account the physiological positive effect of hyperuricemia on kidney and vascular cells and not prescribe urate-lowering therapy? Our observation of two patients, which took place within the randomized patient-oriented study “Development of technology to preserve kidney function in patients with CKD and hyperuricemia”, does not provide direct answers to all these questions, but allows us to assume that hyperuricemia can be compensatory for kidney function, and it will not always be appropriate to actively reduce its level. The article aims to draw attention to the fact that when hyperuricemia causes hyperfiltration to preserve kidney function, lowering its level may be inappropriate for absolutely all patients. And maybe in certain conditions and individual clinical situation, the doctor has the option not to prescribe this type of therapy without negative consequences for kidney function.